2020
DOI: 10.1093/chemse/bjaa029
|View full text |Cite
|
Sign up to set email alerts
|

IL-1Rahigh-IL-4low-IL-13low: A Novel Plasma Cytokine Signature Associated with Olfactory Dysfunction in Older US Adults

Abstract: Inflammation has been implicated in physical frailty, but its role in sensory impairment is unclear. Given that olfactory impairment predicts dementia and mortality, determining the role of the immune system in olfactory dysfunction would provide insights mechanisms of neurosensory decline. We analyzed data from the National Social Life, Health and Aging Project, a representative sample of home-dwelling older US adults. Plasma levels of 18 cytokines were measured using standard protocols (Luminex xMAP). Olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…1432 They reported the presence of EOG responses and functionally mature OSNs at the insertion level of the middle turbinate. Some EOG work also suggested the existence of a specific topographical distribution of ORs with some recording sites only responding to certain odors, 1426 and that the EOG was odorant specific 1427 (and even specific for odorous enantiomers 1433 ). Areas that responded maximally to a pleasant odorant were also likely to respond strongly to other pleasant odorants, and a location that responded maximally to an unpleasant odorant was likely to respond strongly to other unpleasant odorants.…”
Section: F Electro-olfactogrammentioning
confidence: 99%
See 1 more Smart Citation
“…1432 They reported the presence of EOG responses and functionally mature OSNs at the insertion level of the middle turbinate. Some EOG work also suggested the existence of a specific topographical distribution of ORs with some recording sites only responding to certain odors, 1426 and that the EOG was odorant specific 1427 (and even specific for odorous enantiomers 1433 ). Areas that responded maximally to a pleasant odorant were also likely to respond strongly to other pleasant odorants, and a location that responded maximally to an unpleasant odorant was likely to respond strongly to other unpleasant odorants.…”
Section: F Electro-olfactogrammentioning
confidence: 99%
“…179,180,183,1264 Four studies have evaluated inflammatory proteins in non-CRS-related OD. 181,[1265][1266][1267] Schubert et al 1266 found no associations between baseline systemic Creactive protein, IL-6, and TNF-α to subsequent development of OD over 10 years and Darnell et al 1265 found a systemic cytokine profile associated with frailty (high IL-1 receptor antagonist, low IL-4, low IL-13) had significantly higher odds of worse olfaction. Henkin et al 181 found that IL-6 levels were significantly higher in the plasma, saliva, and nasal mucus of hyposmic patients compared with normosmic patients.…”
Section: E Measurement Of Cytokine/mucin Levelsmentioning
confidence: 99%